DO INDONESIAN MIGRANT DOMESTIC WORKERS ENGAGE WITH HOMELAND POLITICS? - Kusumastuti, Ayu (UI Scholars Hub, 2023)
International labour mobility has increased Indonesian female migrant domestic workers' involvement in transnational labour organisations. Because of their precarious work, advocacy and unions are crucial to protecting them overseas. This paper examines the debates on the political activism of Indonesian female domestic workers and discusses the gap that migration scholars have not yet addressed. The study's conceptual core employs the concept of migrant political transnationalism, which generates the intersection of migrant citizenship and receiving country sovereignty. The author has reviewed thirty journals using exclusion and inclusion criteria with a qualitative narrative literature review. Grassroots advocacy for Indonesian domestic workers primarily emerged in Hong Kong. On the one hand, territorial normativity and sovereignty in the receiving country may prohibit migrants from participating in politics. However, they still can engage in extra-electoral politics as non-citizens. Domestic workers advocate for their rights through lobbying, protests, and rallies. On the other hand, electoral political participation in homeland politics, which political transnational scholars rarely discuss, and their contribution to mobilising votes abroad is also necessary. This finding motivates the investigation's research agenda: Do Indonesian female domestic migrant workers engage with their electoral homeland politics?